Iterative Inversion of Normal and Lateral Resistivity Logs in Thin-Bedded Rock Formations of the Polish Carpathians - Michał Wilkosz (Geosciences)
This study investigates the challenges and opportunities associated with improving the vertical resolution of normal and lateral resistivity logs in thin-bedded rock formations. The proposed iterative inversion procedure combines a finite element method forward modeling procedure with a particle swarm optimization algorithm to generate high-resolution models of the rock formation. The performance of the inversion approach was evaluated using synthetic datasets, and the results of the inversion of field data from thin-bedded formations of the Polish Carpathians are presented. This research highlights the potential of modern computational techniques to enhance the utility of historical resistivity logging data in current studies.